The community structure of macroalgae in a low shore mangrove forest in Selangor, Malaysia - Aikanathan, S.; Sasekumar, A. (Kluwer (now part of Springer), 1994)
The macroalgal communities associated with pneumatophores, basal area of tree trunks and sediment surface in the mangrove forest at Sementa, Selangor consisted of nine main species. Biomass, frequency of occurrence and relative cover of the species along a belt transect, showed two major trends, a decrease in these parameters in the landward direction for Colpomenia sp. Gracilaria blodgettii and Gracilaria crassa and an increase in the landward direction for Dictyota dichotoma, Catenella nipae, Rhizoclonium sp. and Bostrichia radicans. Algal dominance varied with substratum. Pneumatophores were dominated by Caloglossa lepreurii and sediment surface by D. dichotoma. The 40 cm zone at the base of tree trunks was dominated by two algal species. The 0–20 cm region above the sediment surface was colonized by C. nipae, while the 20–40 cm region was dominated by Rhizoclonium sp. The study identified the importance of substrate in macroalgal colonization.